2004
DOI: 10.1021/bi036164k
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of Gly 121 in Dihydrofolate Reductase from Escherichia coli:  The Altered Structure of a Mutant Enzyme May Form the Basis of Its Diminished Catalytic Performance

Abstract: The structure and folding of dihydrofolate reductase (DHFR) from Escherichia coli and the mutant G121V-DHFR, in which glycine 121 in the exterior FG loop was replaced with valine, were studied by molecular dynamics simulations and CD and fluorescence spectroscopy. The importance of residue 121 for the chemical step during DHFR catalysis had been demonstrated previously. High-temperature MD simulations indicated that while DHFR and G121V-DHFR followed similar unfolding pathways, the strong contacts between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
82
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 55 publications
11
82
0
Order By: Relevance
“…These results emphasized the role of G121 in packing and stability affecting the enzyme function, via long-range interactions (26,27). Finally, CD and fluorescence spectroscopy studies indicated that the folding pattern of the enzyme was also altered by G121V mutation (6), which is in accordance with substantial effect of G121V on the protein thermal dynamics.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…These results emphasized the role of G121 in packing and stability affecting the enzyme function, via long-range interactions (26,27). Finally, CD and fluorescence spectroscopy studies indicated that the folding pattern of the enzyme was also altered by G121V mutation (6), which is in accordance with substantial effect of G121V on the protein thermal dynamics.…”
supporting
confidence: 60%
“…It catalyzes the reduction of 7,8-dihydrofolate (DHF) to 5,6,7, with the concomitant oxidation of NADPH (nicotinamide adenine dinucleotide phosphate, reduced form) to NADP + , in which a hydride is stereospecifically transferred from the pro-R C4 position of the nicotinamide ring to the si face of the C6 position of pterin. This enzyme helps maintain intracellular pools of THF used in the biosynthesis of purine nucleotides and some amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies of single and multiple mutant E. coli DHFR enzymes illustrate that mutations far from the active site can impact the rate of hydride transfer by introducing non-local structural perturbations and altering the conformational sampling of configurations conducive to the chemical reaction ( Watney et al 2003;Wong et al 2005). Other simulations of mutant E. coli DHFR enzymes have also identified non-local structural effects (Swanwick et al 2004) and alterations in the conformational sampling (Rod et al 2003). Escherichia coli and B. subtilis DHFR enzymes have a sequence identity of 44%, and the experimentally determined X-ray crystallographic structures and hydride transfer rates are similar (Wilson et al in preparation).…”
Section: Introductionmentioning
confidence: 74%
“…Results for mutants of DHFR (22)(23)(24)(25) have been interpreted as showing a central role for protein dynamics in catalysis. However, mutations that affect protein dynamics may actually influence the chemical reaction in other ways (7), such as through changing conformational preferences of the enzyme (26). Strong evidence exists against a direct coupling of large-scale millisecond protein motions to the reaction coordinate during hydride transfer from NADPH to H 2 F (6, 7, 27-29), but the coupling of shortrange promoting enzyme motions to the reaction coordinate in DHFR cannot be excluded experimentally (6,22,27).…”
mentioning
confidence: 99%